(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The temporal and spatial distribution of the current challenges in the field of higher education management shows that these same challenges can be solved through joint efforts that do not contradict international trends in the development of the education sector. The effectiveness of the search for common solutions in the field of education has been proven over the course of a decade, as it also becomes clear that spatial, economic, political, cultural and other factors can be the basis of unity. It is this complex of factors that underlies the formation of the EAEU. Cooperation of the EAEU member states in the field of education has new prospects - not all aspects of this cooperation have been identified and are operating in the current period. Of particular importance is the study of the educational traditions of societies representing different cultures of the EAEU member states, the contours of new dialogues. From this point of view, it is especially important not only to study the Russian education sector, which is completely open for cooperation in the Armenian education sector, but also to study the Kazakhstani education experience, which is possible in terms of identifying new educational and cultural interactions. Cooperation between the EAEU member states has not yet achieved final success in the field of education, which requires new research. If the volume of cooperation between Armenia and Russia, the underlying factors and perspectives are clearer, the same is difficult to say about Kazakhstan. As EAEU member states, apart from examples of private cooperation in the field of education, the ways of cooperation in the field of higher education management have not been expanded and clarified, especially between Kazakhstan and Armenia. This study aims to facilitate the search for cooperation in the field of education management in the EAEU member states. 218 The purpose of the study is to identify the specifics of the indicators of the input of Kazakhstani higher education from the EAEU member states using a specially developed methodology. As part of the study, a new methodology for the comparative analysis of the higher education systems of the EAEU member states was developed, within the framework of which indicators were developed for the first time, thanks to which it is possible to evaluate and analyze the features of education management.